Bioactive Heterocyclic Compounds as Potential Therapeutics in the Treatment of Gliomas: A Review - Hassan, Reyaz; Mohi-ud-din, Roohi; Dar, Mohammad O.; Shah, Abdul Jalil; Mir, Prince Ahad; Shaikh, Majeed; Pottoo, Faheem Hyder (Anti-Cancer Agents in Medicinal Chemistry, 2022)
Abstract: Cancer is one of the most alarming diseases, with an estimation of 9.6 million deaths in 2018. Glioma occurs in glial cells surrounding nerve cells. The majority of the patients with gliomas have a terminal prognosis, and the ailment has significant sway on patients and their families, be it physical, psychological, or economic wellbeing. As Glioma exhibits, both intra and inter tumour heterogeneity with multidrug resistance and current therapies are ineffective. So the development of safer anti gliomas agents is the need of hour. Bioactive heterocyclic compounds, eithernatural or synthetic, are of potential interest since they have been active against different targets with a wide range of biological activities, including anticancer activities. In addition, they can cross the biological barriers and thus interfere with various signalling pathways to induce cancer cell death. All these advantages make bioactive natural compounds prospective candidates in the management of glioma. In this review, we assessed various bioactive heterocyclic compounds, such as jaceosidin, hispudlin, luteolin, silibinin, cannabidiol, tetrahydrocannabinol, didemnin B, thymoquinone, paclitaxel, doxorubicin, and cucurbitacins for their potential anti-glioma activity. Also, different kinds of chemical reactions to obtain various heterocyclic derivatives, e.g. indole, indazole, benzimidazole, benzoquinone, quinoline, quinazoline, pyrimidine, and triazine, are listed.
Keywords: cannabinoids